(untitled) (Western Pacific Surveillance and Response, 2018)
Papua New Guinea has strengthened its surveillance system for tuberculosis (TB) under the National TB Program. This paper provides an overview of TB surveillance data at the national and subnational levels from 2008 to 2016. TB case notification has consistently increased since 2008 with 6184 cases (93 per 100 000 population) in 2008 to 28 598 (359 per 100 000 population) in 2014 and has stabilized since 2014 with 28 244 cases (333 per 100 000 population) in 2016. The population-screening rate for TB rose from 0.1% in 2008 to 0.4% in 2016. Notified cases were dominated by extra-pulmonary TB (EP-TB, 42.4% of all cases in 2016). The proportion of pulmonary TB cases with no sputum test results was high with a national average of 26.6%. The regional variation of case notifications was significant: the Southern Region had the highest number and rate of notified TB cases. Of the nationally reported cases, 26.7% occurred in children. Treatment success rates remained low at 73% for bacteriologically confirmed TB and 64% for all forms of TB in 2016, far below the global target of 90%. For all forms of TB, 19% of patients were lost to follow-up from treatment. An analysis of TB data from the national surveillance system has highlighted critical areas for improvement. A low population-screening rate, a high proportion of pulmonary TB cases without sputum test results and a low treatment success rate suggest areas for improvement in the National TB Program. Our additional subnational analysis helps identify geographical and programmatic areas that need strengthening and should be further promoted to guide the programme’s direction in Papua New Guinea.